Avaliação do processo produtivo e controle de qualidade gel massageador extra forte dr. Green® na salutaris indústria de cosméticos LTDA - Pereira, Luiz Paulo Soares (Universidade Federal Rural do Semi-Árido, 2017)
The Extra Strong Massaging Gel Dr. GREEN® is a new product on the market but has attracted enough attention from its consumers due to its refreshing properties and relief from the feeling of tiredness. The present work seeks to explain the components used in the production of the cosmetic, Extra Strong Massager Gel Dr. GREEN®, brand Salutaris, which is produced in the company's industrial plant, located in the municipality of Mossoró. The present work will also portray the quality tests required by the competent body, ANVISA (Agência Nacional de Vigilância Sanitária), for its later commercialization. The process of production of the cosmetic under analysis was followed in its completeness, beginning with its manufacturing / production, passing the laboratory tests (always being in agreement with the quality control), until arriving at the sector of packaging of the product, being this one the last step only occurs after the release of the same, after having all the results and confeir if they are according to the specifications.
Monografia
Keywords: Cosméticos; Gel; Qualidade; Cosmetics; Quality; ENGENHARIAS::ENGENHARIA QUIMICA